2018
DOI: 10.1093/eurpub/cky030
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity with body mass index, waist circumference and incidence of obesity in older adults

Abstract: LTPA was inversely associated with BMI, WC and incidence of general and abdominal obesity. The finding that low-intensity LTPA was inversely related to BMI and the incidence of obesity is of particular importance because this level of physical activity could be a feasible option for many older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 38 publications
5
20
1
1
Order By: Relevance
“…In this study, we found an inverse association between BMI and physical activity. This is consistent with previous studies and suggest the need for weight reduction among individuals with multimorbidity [41,42]. Also, we found that higher fruits and vegetable consumption was associated with meeting recommended PA.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found an inverse association between BMI and physical activity. This is consistent with previous studies and suggest the need for weight reduction among individuals with multimorbidity [41,42]. Also, we found that higher fruits and vegetable consumption was associated with meeting recommended PA.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, studies have revealed the independent associations of obesity and other related high-risk body measures with physical inactivity. [64][65][66][67] Results of the statistical tests on interactions of obesity-related measures with physical activity in our study show that multimorbidity was more prevalent among older adults who were obese/overweight or at risk of waist to hip ratio and waist circumference with non-performance of any physical activity. The findings of the current analysis which apply to an older population of a developing country highlight the urgent need for further investigation of the effectiveness of physical activity in the management of chronic diseases in lowincome and middle-income countries.…”
Section: Discussionmentioning
confidence: 58%
“…Five decades ago, the Spanish diet was a typical example of the Mediterranean diet, however, lately, Spanish consumers have moved away from that pattern [76]. Previous research, among others, the PREvention con DIeta MEDiterranea (PREDIMED) suggested that better adherence to the Mediterranean diet pattern together with a regular physical activity exerts a greater impact in lowering obesity and all-cause mortality [77,78,79,80,81]. With respect to the dairy products and precisely yoghurts, which form part of Mediterranean diet, it is well demonstrated that whole-fat and low-fat yoghurt consumption is associated with a reduced risk of general obesity [77,82] and also abdominal obesity [83,84].…”
Section: Discussionmentioning
confidence: 99%